The function of ORAOV1/LTO1, a gene that is overexpressed frequently in cancer: Essential roles in the function and biogenesis of the ribosome - Zhai, Chao; Li, Y.; Mascarenhas, Claire; Lin, Qiushi; Li, Kuoyu; Vyrides, Ioannis; Grant, Chris M.; Panaretou, Barry (My University, 2014)
ORAOV1 (oral cancer overexpressed) is overexpressed in many solid tumours, making a key contribution to the development of cancer, but the cellular role of ORAOV1 is unknown. The yeast orthologue of this protein is encoded by the hitherto uncharacterized essential gene, YNL260c. Expression of ORAOV1 restores viability to yeast cells lacking YNL260c. Under nonpermissive conditions, our conditional mutants of YNL260c are defective in the maturation of the 60S ribosomal subunit, whereas maturation of the 40S subunit is unaffected. Also, initiation of translation is abrogated when YNL260c function is lost. YNL260c is indispensible for life in oxygen, but is nonessential under anaerobic conditions. Consequently, the toxic affects of aerobic metabolism on biogenesis and function of the ribosome are alleviated by YNL260c, hence, we rename YNL260c as LTO1; required for biogenesis of the large ribosomal subunit and initiation of translation in oxygen. Lto1 is found in a complex with Rli1/ABCE1, an ATP-binding cassette (ABC)-ATPase bearing N-terminal 4Fe-4S clusters. Like Lto1, the Rli1/ABCE1 4Fe-4S clusters are not required for viability under anaerobic conditions, but are essential in the presence of oxygen. Loss of Lto1 function renders cells susceptible to hydroperoxide pro-oxidants, though this type of sensitivity is specific to certain types of oxidative stress as the lto1 mutants are not sensitive to an agent that oxidizes thiols. These findings reflect a functional interaction between Lto1 and the Rli1/ABCE1 4Fe-4S clusters, as part of a complex, which relieves the toxic effects of reactive oxygen species (ROS) on biogenesis and function of the ribosome. This complex also includes Yae1, which bridges the interaction between Lto1 and Rli1/ABCE1. Interactions between members of this complex were demonstrated both in vivo and in vitro. An increased generation of ROS is a feature shared by many cancers. The ORAOV1 complex could prevent ROS-induced ribosomal damage, explaining why overexpression of ORAOV1 is so common in solid tumours.
Keywords: Fe-S cluster; Ribosome biogenesis; Squamous cell carcinoma; Translation